2014
DOI: 10.2174/1871526513666131129155708
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on the Mechanism of Action of Artemisinin Antimalarials: Part 1 - The 'Carbon Radical' and 'Heme' Hypotheses

Abstract: The isolation of artemisinin from the traditional medicinal herb qīng hāo (Artemisia annua), its characterization as a peroxide and preparation of the derivatives dihydroartemisinin, artemether and artesunate in the 1970s and 1980s by Chinese scientists under the umbrella of Project 523 collectively represents one of the great events in medicine in the latter third of the 20(th) Century. Artemisinins have become the most important component of chemotherapy of malaria: although used initially in monotherapy, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 0 publications
1
62
0
1
Order By: Relevance
“…Although it remains to be precisely established how artemisone exerts its cytotoxic effect, it is very likely that it enhances generation of reactive oxygen species (ROS) [12,13] and, as in other cases involving selective cytotoxicity in cancer cells induced by oxidative stress [36,37,38] …”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it remains to be precisely established how artemisone exerts its cytotoxic effect, it is very likely that it enhances generation of reactive oxygen species (ROS) [12,13] and, as in other cases involving selective cytotoxicity in cancer cells induced by oxidative stress [36,37,38] …”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Subsequently, it was found to be active against other parasites [6], and to possess antitumour properties [7,8,9,10]. Although the mechanism of action is popularly ascribed to cytotoxic free radicals arising via reaction of iron with the peroxide within the 1,2,4-trioxane [11], it is more likely that the intrinsic oxidant properties of the peroxide perturb intracellular redox homeostasis by interrupting electron flow to crucial intracellular reductants such as glutathione responsible for maintaining redox homeostasis in the stressed environment of the pathogen, a process that will be enhanced in the presence of iron [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Significantly,i th as been shown that attachment of lipophilic steroidal groups to tetraoxanesp rovides compounds such as 6 that are also strikingly active against Mtb (Figure 2). [14] However,t he evident cytotoxicity of these compounds precludes their further development Under ap rogram designed to developn ew triple drug combinations for the treatment of malaria, tuberculosis, and toxoplasmosis, [15] we are preparing and evaluating efficacieso f drug combinations whichh ave oxidanta nd redox properties, respectively [16] coupled with at hird partnerw ith ad ifferent mode of action. The third partner drug being considered in the first instance incorporates a4 (1H)-quinolones caffold.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, accumulation of toxic free heme from erythrocyte destruction during malaria infection could induce oxidative stress from the hydroxyl radical production via Fenton/Harber-Weiss reaction followed by liver injury [18]. Moreover, during malaria infection, overproduction of oxidized low density lipoprotein can trigger adverse effect in vascular lesion, reactive oxygen species, and liver cell damage [19].…”
Section: Discussionmentioning
confidence: 99%